Male-emitted benzaldehyde acts as an olfactory antagonist, disrupting moth sex pheromone communication - Dongdong Sun; Yutong Zhang; Xiaoqing Wang; Yong Wang; Guirong Wang; Yang Liu (Proceedings of the National Academy of Sciences, 2026)
Sexual competition among males drives the evolution of diverse reproductive strategies in insects, including the use of chemical signals to influence the behavior of rivals. Yet, the role of chemically mediated male–male competition remains underexplored in moths. Here, we show that male Mythimna separata moths emit benzaldehyde (BA) during courtship competition to disrupt rivals’ ability to detect the female sex pheromone (Z)-11-hexadecenal (Z11-16:Ald). BA release is socially regulated and increases markedly under high male density and in the presence of female-derived cues or synthetic Z11-16:Ald. Electrophysiological recordings and calcium imaging assays indicate that BA suppresses peripheral olfactory responses by competitively inhibiting the Z11-16:Ald-specific receptor MsepPR3 at the ligand-binding site, as confirmed through structural modeling and dynamics simulations. This receptor-level antagonism represents a mechanism of olfactory disruption during reproductive competition. Our findings reveal a context-dependent strategy through which male moths disrupt rival chemosensory perception, providing insight into the evolution of sexual signaling and suggesting receptor-targeted approaches for future pest management applications.